Exploring Health and Financial Literacy in Patients With Peripheral Nerve Injury: A Cross-Sectional Analysis of Patients Treated Surgically - Jake H. Goldfarb, BS; Zachary D. Randall, BS; David M. Brogan, MD, MSc; Christopher J. Dy, MD, MPH (Journal of Hand Surgery Global Online, 2025)
Purpose: Health literacy influences patient outcomes and recovery in musculoskeletal conditions. Although financial distress is common after orthopedic injuries, the role of financial literacy in these patients is unknown. We aimed to evaluate health and financial literacy in patients recovering from peripheral nerve injuries (PNI). Methods: After obtaining institutional review board approval, this cross-sectional study surveyed 21 patients with either PNI or brachial plexus injuries via phone. Two validated instruments were administered: the Health Literacy Questionnaire, comprising 44 items across nine independent domains, and a 23-item Financial Literacy Questionnaire assessing a range of financial literacy concepts. Descriptive statistics summarized scores on both surveys. Results: Participants had a mean age of 52.3 ± 15.8 years; 38% were women. The Health Literacy Questionnaire results demonstrated uniformly high health literacy across all domains, with the highest scores observed in domains related to active engagement with health care providers, understanding health information, and social support. In contrast, financial literacy, measured by the overall percentage of correct responses on the Financial Literacy Questionnaire, averaged 70% ± 20% (range: 21.7% to 91.3%), indicating moderate financial literacy with substantial interpatient variability. Conclusions: Patients recovering from PNI possess high levels of health literacy across nine different domains, comparable with populations with chronic conditions such as psoriasis, heart failure, and those undergoing dialysis. However, moderate and variable financial literacy suggests that despite effective health care system navigation, many patients may be less equipped for the financial challenges associated with their injury. These findings highlight the potential benefit of integrating targeted financial education into the perioperative management of PNI patients. Type of study/level of evidence: Therapeutic IV.